New insights into Eragrostis curvula’s sexual and apomictic reproductive development - Pasten, María Cielo; Carballo, José; Díaz, Alejandra Raquel; Mizzotti, Chiara; Cucinotta, Mara; Colombo, Lucia; Echenique, Viviana Carmen; Mendes, Marta Adelina (Frontiers in Plant Science, 2025)
Apomixis, defined as asexual propagation by seeds, is considered of great importance for agriculture as it allows the fixation of desired traits and its propagation through generations. Eragrostis curvula (Schrad.) Ness, is a perennial grass that comprises a polymorphic complex including sexual and diplosporous apomictic cytotypes, where all apomicts are polyploids. In this study we present the first detailed description of female and male gametophyte development in E. curvula through confocal laser microscopy, contrasting three genotypes: the fully apomictic Tanganyika, the facultative apomictic Don Walter, and the sexual OTA-S. Moreover, we have studied the localized expression of a gene known as SQUAMOSA PROMOTER BINDING PROTEIN-LIKE7 (SPL7), that was found to be differentially expressed in contrasting genotypes of E. curvula. This gene had been previously linked with flower development and abiotic stresses in several species, thus, in situ hybridizations were carried out in the model plant Arabidopsis thaliana, as well as in sexual and apomictic E. curvula genotypes. Our microscopy analysis has led to the identification of specific morphological characteristics for each genotype, mainly depicting a larger ovule in the sexual genotype’s reproductive development after the meiosis stage. These results reveal potentially important features, which could be used for a simple identification of genotypes. Moreover, differential expression of the gene SPL7 was detected, specifically determining an overexpression of the gene in the sexual genotype. These results demonstrated that it could be an interesting candidate to understand the mechanisms behind apomictic development.